THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL ATTITUDE, FINANCIAL MANAGEMENT BEHAVIOR AND FINANCIAL INCLUSION ON THE PERFORMANCE OF MSMES IN SEMARANG CITY - Rissa Anie Safitri; Andwiani Sinarasri (Value Added : Majalah Ekonomi dan Bisnis, 2026)
This study aims to find out the factors that affect the performance of MSMEs with financial literacy, financial attitude, financial management behavior, and financial inclusion as independent variables. This research is of a quantitative type. The population and sample used were Semarang City MSME actors, which were selected through convenience sampling techniques  so that the respondents of this study amounted to 250 MSMEs. The research data was obtained through a field survey by distributing questionnaires to MSME actors in Semarang City. This study uses primary data analyzed by multiple linear regression data analysis technique using SPSS version 26. The findings of this study found that the performance of MSMEs was positively and significantly influenced by financial literacy and financial management behavior, while financial attitude and financial inclusion had no influence on the performance of MSMEs.